The Role of Transcendental Communication in Enhancing Morals: A Study of Students at State Islamic Religious Universities in Indonesia - Bunyamin; Khalif Oktifan Yani; Rayhaniah, Sri Ayu (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
This study aims to identify the role of transcendental communication in improving the morality of students at State Islamic Religious Colleges (PTKIN) in Indonesia. Transcendental communication, through prayer, dhikr, and reading the Quran, is an important element in the formation of student character, especially in their relationship with Allah, themselves, others, and the environment. This study is motivated by the importance of character education in Islam that needs to be applied consistently in the PTKIN environment. This study uses a qualitative method with a phenomenological approach, which involves in-depth interviews with PTKIN students. Additional data were obtained through documentation and observation of religious activities on campus. The results of the study indicate that transcendental communication significantly improves students' morality , especially in terms of discipline, patience, empathy, and awareness of responsibility towards the environment. The recommendation from this study is for PTKIN to strengthen religious programs based on worship and create a campus environment that supports the consistency of student worship. The results of this study provide a real contribution by offering an empirical basis for PTKIN to integrate transcendental communication into the curriculum and religious programs in order to form the character of students with noble morals, thus supporting the creation of an academic environment that is oriented towards spiritual and moral values.